APC/C is essential for hematopoiesis and impaired in aplastic anemia - Wang, Jia (Oncotarget, 2017)
Anaphase promoting complex/cyclosome (APC/C) is essential for cell cycle progression. Recently, its non-mitotic functions were also reported but less studied in several tissues including hematopoietic cells. Here, we developed an inducible Anapc2 (a core subunit of APC/C) knockout mice. The animals displayed a fatal bone marrow failure within 7 days after knockout induction. Their hematopoietic stem and progenitor cells (HSPCs) demonstrated a sharp decline and could form little colony. Further, the results of BrdU label-retaining cell assay showed that the dormant HPSCs lost rapidly. Analysis of cell cycle regulators, Skp2, P27, Cdk2, and Cyclin E1, suggested that these quiescent stem cells underwent a shift from quiescence to mitosis followed by apoptosis. We next detected Anapc2-expression in the CD34(+) HSPCs of patients with aplastic anemia. CD34(+) cells were markedly decreased in the bone marrow and Anapc2-expression in the residual CD34(+) cells was undetectable, suggesting that APC/C was deficient and might have a relationship with the pathogenesis of aplastic anemia.